Spatial Market Integration of Arhar (Split) Wholesale Prices in India : Application of Vector Error Correction Model - Savadatti, Pushpa (Indian Journal of Marketing, 2018)
The present study aimed at analysing the spatial market integration of arhar markets in India, based on the monthly wholesale prices of arhar (split) in Mumbai (Maharashtra), Hyderabad (Telangana), Chennai (Tamil Nadu), and Bangalore (Karnataka) markets for the period from January 2011 to December 2015. The Augmented Dickey Fuller test indicated that Mumbai, Chennai, and Hyderabad arhar market price series were I(1), but that of the Bangalore arhar market, the price series were I(2) ; hence, further analysis was carried out for these three markets only. The results of Johansen co-integration test indicated that three arhar markets were significantly co-integrated with each other. The VECM model revealed that speed of adjustment for Mumbai and Hyderabad markets was statistically significant, but for Chennai market, it was insignificant, though having an expected negative sign. The Granger causality test indicated unidirectional relationship between the markets. The speed of price transmission was slow for all the three markets. This may be due to reasons such as lack of proper infrastructural facilities, paucity of institutional arrangements, transport costs, and absence of good government policies. This calls for more efforts on the part of the government in removing these constraints so that there will be efficient flow of price information among the domestic arhar markets in India.